Upaya Penggunaan Media Pembelajaran Visual (LCD) dalam Peningkatan Hasil Belajar Mata Pelajaran Ekonomi pada Siswa Kelas XI A SMA Negeri 1 Keruak: Efforts to Use Visual Learning Media (LCD) to Improve Learning Outcomes in Economics Subjects in Class XI A Students of SMA Negeri 1 Keruak - Rijnan (Pendidikan Al-Gafari, 2025)
Basically every child needs education, because with education children can develop their interests and talents. One effort to develop these talents and interests is through a formal or non-formal institution.This research aims to determine the increase in student activity and learning outcomes through the use of LCD visual learning media in class XI A of SMA Negeri 1 Keruak. The subjects in this research were 27 students in class XI A of SMA Negeri 1 Labangka. This type of research is classroom action research (PTK) which has been carried out in 2 cycles, each cycle consisting of planning, action, observation and reflection stages. The data obtained in this research include: Percentage of student learning activity, percentage of Teacher Active Performance Activity (APKG) and student learning outcomes taken from giving test questions at the end of the cycle, teacher ability in learning taken from the observation sheet and student activity in learning taken from the observation sheet. Indicators of success in this research are: (1) if the average value of student learning outcomes is ≥ 75, classical learning completeness ≥ 80%, with individual completeness of 75 (2) if student activity in learning increases as measured by looking at the student observation sheet. From the results of the study it can be concluded that the use of LCD visual learning media can improve a). Students' economic learning outcomes on the subject of Viscal Policy in the field of taxation in class XI A of SMA Negeri 1 Keruak. In cycle I, the average student score was 67 and increased in cycle II, namely: 86. b). Increased student learning activities in cycle I, namely: 19.5% with a low category, but there was an increase in cycle II, namely: 42% with a sufficient category. c). Increased teacher performance from cycle I data, namely: 60 (CD) increased in cycle II to 93 (A). d). Students who completed learning from cycle I were 48% increasing to 89% in cycle II.